2014
DOI: 10.1371/journal.pone.0085466
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Heart Failure Risk Tool: The Barcelona Bio-Heart Failure Risk Calculator (BCN Bio-HF Calculator)

Abstract: BackgroundA combination of clinical and routine laboratory data with biomarkers reflecting different pathophysiological pathways may help to refine risk stratification in heart failure (HF). A novel calculator (BCN Bio-HF calculator) incorporating N-terminal pro B-type natriuretic peptide (NT-proBNP, a marker of myocardial stretch), high-sensitivity cardiac troponin T (hs-cTnT, a marker of myocyte injury), and high-sensitivity soluble ST2 (ST2), (reflective of myocardial fibrosis and remodeling) was developed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 22 publications
3
95
0
5
Order By: Relevance
“…W ostatnich dekadach opracowano wiele różnych skal ryzyka dla różnych populacji pacjentów z HF [36][37][38][39][40][41], które są częściowo dostępne w formie interaktywnych aplikacji online. Skale ryzyka oparte na wielu zmiennych mogą być pomocne w przewidywaniu ryzyka zgonu, ale mają mniejsze znaczenie dla oceny ryzyka ponownej hospitalizacji pacjenta z HF [37,38].…”
Section: Rokowanieunclassified
“…W ostatnich dekadach opracowano wiele różnych skal ryzyka dla różnych populacji pacjentów z HF [36][37][38][39][40][41], które są częściowo dostępne w formie interaktywnych aplikacji online. Skale ryzyka oparte na wielu zmiennych mogą być pomocne w przewidywaniu ryzyka zgonu, ale mają mniejsze znaczenie dla oceny ryzyka ponownej hospitalizacji pacjenta z HF [37,38].…”
Section: Rokowanieunclassified
“…Working under flow conditions allowed us to compare the efficiency of two different detection strategies: measurement of steady state currents and generation of stop-flow peaks (in which flow retention for a fixed time results in building up of the enzymatic product, improving detection significantly). The results obtained show that the microfluidic platform described here is capable of multiplexed biomarker determination, which is crucial for diagnosis and stratification of heart diseases (Lupón et al, 2014).…”
Section: Introductionmentioning
confidence: 80%
“…Th e Barcelona Bio-Heart Failure Risk Calculator incorporating ST2, N-terminal pro BNP, and troponin T biomarkers allowed better prediction of death among HF patients (7). Compared to the Seattle Heart Failure Model, the Penn Heart Failure Study found that a multimarker score incorporating biomarkers increased the ability to predict adverse outcomes in ambulatory patients with chronic HF (8).…”
Section: Discussionmentioning
confidence: 99%